Optimised processing of faba bean (Vicia faba L.) kernels as a brewing adjunct. Issue 1 (28th December 2020) - Black, Kirsty; Tziboula‐Clarke, Athina; White, Philip J.; Iannetta, Pietro P.M.; Walker, Graeme
Abstract : Pulse ( Fabaceae ) grains, such as peas and beans, are derived from crops that are usually cultivated in the absence of mineral nitrogen fertiliser as these crops can obtain their nitrogen requirement naturally from the air via biological nitrogen fixation. Therefore, pulses present a significantly lower greenhouse gas (GHG) footprint than crops demanding nitrogen fertiliser, whilst also offering significant quantities of starch for the brewing and distilling industries. Mitigation of agriculture derived GHG emissions through utilisation of pulses can have a positive environmental impact. To this end, the potential of exploiting dry, dehulled faba bean ( Vicia faba L.) kernel flour as an adjunct for beer production was evaluated. The impact of different temperature regimes and commercial enzymes were assessed for their effect on wort: viscosity; run‐off rate; primary amino nitrogen content and, fermentability. Faba beans demonstrated insufficient endogenous enzyme capacity for starch conversion and generated a viscous wort. However, using a stepped temperature mashing regime and exogenous enzyme additions, the faba bean wort was comparable in processability and fermentability to that of 100% malted barley wort. The faba based beer and co‐product qualities demonstrate the environmental, nutritional and commercial potential of pulses in brewing. © 2020 The Authors. Journal of the Institute of Brewing published by John Wiley & Sons Ltd on behalf of The Institute of Brewing & Distilling